IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH STORY BOARD GAME (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This journal is made based on the action research in order to improve students’ speaking ability by using story board game. This action research was conducted in SMA Negeri 1 Grabag. The action research was carried out in some steps. Those steps were pre-elimination test, conducting the cycle starting with planning and action, observing and reflecting. As data source, observation sheets and questionnaire are used in this research. The implementation of the game was reflected on the classroom activity and the result of observation sheets. While, he score was gotten from the scoring system. By using this game, the students’ speaking ability increased. Some aspects in speaking assessment were also increased. The analysis of observation sheets and questionnaire give more description about the implementation of this game. According to the study, it can be concluded that by using this game in speaking class, students’ speaking ability can be improved. This game is good media to help the students in speaking English in more enjoyable way.